Kepuasan Hidup Pekerja Perempuan: Sebuah Tinjauan Konseptual - Muthia Pramesti; Isbandi Rukminto Adi; Riani Rachmawati (Direktorat Riset dan Pengabdian Kepada Masyarakat, 2021)
This paper aims to conduct a conceptual study of factors that drive lifesatisfaction in the work domain for female workers. They experience severalproblems related to human resource policies related to their personal and worklife. The dual role as breadth winner and housewife often take place. Lifesatisfaction is interesting to be discussed due to the well-being challenges forfemale workers. The framework is built by “Top-Down” and “Bottom-Up”theory. The author conducted an electronic-based data search from 58 articlesduring the 2019-2021 period. Several factors affect job satisfaction, such asneed fulfilment, self-development and work pressure. In the discussionsection, it will explain the factors driving workers' life satisfaction to life,especially for female workers.